2021
DOI: 10.14744/semb.2021.95825
|View full text |Cite
|
Sign up to set email alerts
|

Can simple non-invasive fibrosis models determine prognostic indicators (fibrosis and treatment response) of primary biliary cholangitis?

Abstract: Objective: The fibrosis stage during diagnosis and the response to ursodeoxycholic acid in the 1 st year of treatment are considered to be prognostic indicators in primary biliary cholangitis (PBC). Determining these indicators with non-invasive models can enable the risk of liver failure to be monitored with continuous variables from the moment of diagnosis. The aim of this study was to evaluate the diagnostic performance of non-invasive models for determining the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among these, APRI, FIB-4, and elastography are widely used methods. [ 7 , 18 , 19 ] The relationship between PBC and many fibrosis markers has been evaluated. [ 7 , 20 , 21 ] In a study involving 107 patients diagnosed with PBC, erythrocyte distribution width, FIB-4, albumin, and platelet values were found to be associated with fibrosis, among which FIB-4 had the highest sensitivity and specificity for distinguishing histological severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, APRI, FIB-4, and elastography are widely used methods. [ 7 , 18 , 19 ] The relationship between PBC and many fibrosis markers has been evaluated. [ 7 , 20 , 21 ] In a study involving 107 patients diagnosed with PBC, erythrocyte distribution width, FIB-4, albumin, and platelet values were found to be associated with fibrosis, among which FIB-4 had the highest sensitivity and specificity for distinguishing histological severity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In a recent study, the S-index calculated with a special formula consisting of GGT, platelets, and albumin was found to be significantly higher in patients with PBC in the advanced fibrosis group (F3-4) according to the Scheuer system. [ 19 ] Based on this information, we hypothesized that GPR, which can be calculated more easily using GGT and platelets among the parameters used in the S-index in patients with PBC, could be an effective marker for determining fibrosis and cirrhosis. In our study, FIB-4 and GPR levels were found to be statistically significantly higher in the advanced fibrosis group.…”
Section: Discussionmentioning
confidence: 99%